2017
DOI: 10.1002/14651858.cd012143.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Direct-acting antivirals for chronic hepatitis C

Abstract: Overall, DAAs on the market or under development do not seem to have any effects on risk of serious adverse events. Simeprevir may have beneficial effects on risk of serious adverse event. In all remaining analyses, we could neither confirm nor reject that DAAs had any clinical effects. DAAs seemed to reduce the risk of no sustained virological response. The clinical relevance of the effects of DAAs on no sustained virological response is questionable, as it is a non-validated surrogate outcome. All trials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 333 publications
3
57
1
1
Order By: Relevance
“…4 Despite some recent controversial results from a Cochrane meta-analysis, which was unable to determine the effect of DAAs on hepatitis C-related morbidity and all-cause mortality, data from observational studies and trials using surrogate outcomes show that modern pan-genotypic DAA regimens are efficacious against HCV-related morbidity and mortality, also in patients with early fibrosis/non-advanced liver disease. 5,6 Notwithstanding, HCV prevalence is declining in the general population, HCV incidence is increasing between special populations such as persons who injects drugs (PWID), men who have sex with men (MSM) and prisoners. In this article, we will review the perspective of HCV eradication, es- in the target 3.3 stated: "…end the epidemics of AIDS, tuberculosis, malaria and neglected tropical diseases and combat hepatitis, water-borne diseases and other communicable diseases…".…”
Section: Introductionmentioning
confidence: 99%
“…4 Despite some recent controversial results from a Cochrane meta-analysis, which was unable to determine the effect of DAAs on hepatitis C-related morbidity and all-cause mortality, data from observational studies and trials using surrogate outcomes show that modern pan-genotypic DAA regimens are efficacious against HCV-related morbidity and mortality, also in patients with early fibrosis/non-advanced liver disease. 5,6 Notwithstanding, HCV prevalence is declining in the general population, HCV incidence is increasing between special populations such as persons who injects drugs (PWID), men who have sex with men (MSM) and prisoners. In this article, we will review the perspective of HCV eradication, es- in the target 3.3 stated: "…end the epidemics of AIDS, tuberculosis, malaria and neglected tropical diseases and combat hepatitis, water-borne diseases and other communicable diseases…".…”
Section: Introductionmentioning
confidence: 99%
“…Direktni antivirusni lijekovi 7 Cochrane sustavni pregled primjene direktnih antivirusnih lijekova u liječenju kroničnog hepatitisa C predstavlja zajednički recentan rad koji je u trenutku pisanja ovog preglednog članka u postupku publikacije. Plod je suradnje više autora iz različi-tih europskih zemalja pod okriljem Cochrane hepatobilijarne grupe u koji su uključeni i članovi naše Cochrane grupe.…”
Section: Pegilirani Interferon I Ribavirinunclassified
“…Late viral relapses are extremely rare after successful treatment with DAAs . However, a recent exhaustive systematic review underlined the absence of evidence to determine the effect of sustained viral response on long‐term outcome . Regarding neurobiological consequences, it has been suggested that the infected microglial cells may increase secretion of pro‐inflammatory cytokines such as tumour necrosis factor‐α (TNF‐α) or interleukins (IL), which have been associated with the physiopathology of depressive and cognitive symptoms …”
Section: Introductionmentioning
confidence: 99%